POLÍTICAS DE FORMAÇÃO INICIAL DE PROFESSORES PARA OS PRIMEIROS ANOS NO BRASIL E NA ARGENTINA: UM ESTUDO COMPARADO - BOBATO, FRANCINE CORDEIRO (2015)
This work was produced to meet the Master’s Degree in Education requirements in the Graduate Program of Education of the Midwestern State University (UNICENTRO). It offers the results of research with the objective of comparing the policies for the initial training of elementary school teachers in Brazil and Argentina. Provided the current demands of the globalization process, the compared perspective allowed for the understanding, verification and interpretation of ways in which two higher education institutions in these countries conceive the elementary-school teacher training process. In addition to the review of theory, legal documents from both countries were consulted, as well as interviews with teachers and coordinators who work in the training of the future teachers in both countries. The corpus was analyzed from the compared education perspective according to Aguilar (2013), Bonitatibus (1989), Ferreira (2001, 2008), Franco (2000), Gorostiaga (2013) and others. The option for comparative education procedures has been valid because it offers a rich field for the consistent and deep understanding of a foreign educational system in confrontation with ours, so as to avoid ethnocentrism, idiosyncrasy, and fostering a critical assessment. The economic, political, social and cultural transformations under the aegis of the globalization process have appeared worldwide and had a great impact in the educational field, given the reforms that were implemented in several countries. In this context, the Latin American countries were targets of the guidelines established by multilateral organizations aiming to improve education. In the global process that prompted groupings of countries, the regional Latin American grouping called Southern Common Market – MERCOSUL has proposed the social, political and economic integration in pursuit of strengthening their economies. Within this group, we have focused on the Educational Sector of MERCOSUL – SEM, which recognizes education as a privileged space of integration among the Latin American peoples. Out of the group member states, Brazil and Argentina were selected due to their similarities and partnerships. The objects of research were the undergraduate teacher training program of Pedagogy at UNICENTRO, in Irati, Paraná, Brazil, and the Educational Sciences Program at Universidad Tres de Febrero (UNTREF), in Buenos Aires, Argentina. The study revealed that both countries design their educational policies in accordance with the demands that are posed to the profession of teaching after the educational reforms. Brazil and Argentina experience a universalization of the basic education and conceive of the teaching activity as a distinguishing feature in the quality of the educational process. In the attempt of promoting educational advance, both countries advocate policies that point in this direction. However, teacher training still is a great challenge for the two countries, although the Brazilian situation features greater gaps than the Argentinian one.